Belit Cement Based on Concrete Recyclate - Kulísek, Karel; Gazdič, Dominik; Dvořák, Karel; Magrla, Radek (Key Engineering Materials, 2016)
Main phase of belite cement is β-C2S. This modification is distinguished by low hydration speed compared to alite, which is main mineral of commonly produced cement. It is possible to increase the low hydration speed by modification of raw mixture by potassic ions, which basically change the belite structure. It leads to the content increase of internal free energy and therefore its reactivity too. Positioning of potassic ions in produced clinker is solved by combined burning.